2008
DOI: 10.32725/jab.2008.015
|View full text |Cite
|
Sign up to set email alerts
|

Silver or silver nanoparticles: a hazardous threat to the environment and human health?

Abstract: Nanotechnology is a rapidly growing science of producing and utilizing nano-sized particles that measure in nanometers. These nanomaterials are already having an impact on health care. Now-a-days we are using nanoproducts in various fields. Of these, silver nanoparticles are playing a major role in the field of nanotechnology and nanomedicine.Their unique size-dependent properties make these materials superior and indispensable as they show unusual physical, chemical and biological properties. Silver nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
258
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(269 citation statements)
references
References 79 publications
4
258
0
7
Order By: Relevance
“…The predicted environmental concentration (PEC) of AgNPs in surface water, which is the main exposure route, is 0.088-10,000 ng L À1 , and the maximum estimated PEC in wastewater treatment plant effluent is 17 lg L À1 (Maurer-Jones et al, 2013). For these reasons, there is a growing interest in the potential risks of AgNPs (Luoma, 2008;Panyala et al, 2008;Quadros and Marr, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The predicted environmental concentration (PEC) of AgNPs in surface water, which is the main exposure route, is 0.088-10,000 ng L À1 , and the maximum estimated PEC in wastewater treatment plant effluent is 17 lg L À1 (Maurer-Jones et al, 2013). For these reasons, there is a growing interest in the potential risks of AgNPs (Luoma, 2008;Panyala et al, 2008;Quadros and Marr, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Chitosan holograms were fabricated initially with silver nanoparticles, utilising laser ablation (results not shown); however, their questionable toxicity and potential cause of argyrosis (Panyala and Havel, 2008) lead to the introduction of gold nanoparticles instead. The SEM and TEM analysis of the chitosan hologram fabricated with gold nanoparticles revealed a smooth surface, an approximate height of 1 μm in the xerogel state and nanoparticles in the size range of 5-20 nm arranged in apparent fringes (supplementary material).…”
Section: Fabrication Of Holograms Based On Biocompatible and Biodegramentioning
confidence: 99%
“…This creates a serious problem because recent studies showed that silver nanoparticles can be toxic to plants, microorganisms and invertebrates (Gorth et al 2011;Kumari et al 2009;Scown et al 2010). Moreover, it is hypothesized that both silver forms: nanoparticles and ions, under uncontrolled concentration can be toxic to mammalian and plants (Panyala et al 2008). The leaching of ions from nanoparticles was investigated and described in the literature (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Silver nanoparticles cause the destruction of the pathogens by the perforation of the biological membrane, changes in the surface potential of cells, and the inhibition of the uptake of water and microelements from the environment (Rai et al 2009). It is assumed that the release of silver ions from nanoparticle surfaces plays a dominant role in their biological activity (Kittler et al 2010;Panyala et al 2008). The leached silver ions can interact with the thiol groups of proteins resulting in inactivation of vital enzymes and disrupting the replication of DNA in biological cells (Hosseinkhani et al 2008;Neal 2008).…”
Section: Introductionmentioning
confidence: 99%